(untitled) (Journal of Geography and Environmental Management, 2025)
This article discusses apitourism, which is one of the promising areas for the development of tourism in Kazakhstan. Apitourism is a type of tourism associated with bees, with their products and their tasting and consumption. Apitourism is one of the types of tourism that is closely linked to the ecosystem of our world. By developing apitourism, we not only learn and use the wellness potential of bee products, but also instill love and care for nature, as well as develop the qualities of tourists’ responsibility to the environment. The purpose of this study was the prospect of the development of this type of tourism, as well as the possibility of its development in Kazakhstan. As a result of the research, a comparative analysis of international experience in apitourism development was conducted, along with a sociological survey, and a SWOT analysis assessing the prospects for the development of apitourism in Kazakhstan. To move beyond general recommendations about adopting international practices, several concrete steps are proposed. First, pilot tourist routes should be developed in regions with strong beekeeping potential, such as East Kazakhstan and Zhetisu. These routes could include the installation of small apiary houses, designated sanitary zones, and informational stands to educate visitors. A key focus should be placed on human capital: launching short-term training courses and certification programs for beekeepers, tour guides, and agro-tourism operators at universities and specialized training centers. Additionally, an online platform could be created to facilitate experience-sharing between beekeepers and travel agencies. Drawing from international best practices, it would also be beneficial to send specialists abroad for practical training in beekeeping and tourism integration